Analysis of Waste Minimization Challenges to European Food Production Enterprises - Gunta Grinberga-Zalite; Andra Zvirbule (Ital Publication, 2022)
Economic growth increases the pressure on environmental issues, thus highlighting the importance of waste minimization processes. The waste management approaches in most European countries have so far been relatively little studied and compared at the micro level. The main objective of the current research is to analyze the challenges of waste minimization in European food industry enterprises and identify good practices in the selected countries. The research used a mixed-method methodology, combining both qualitative and quantitative methods, thus providing an in-depth insight into food enterprises’ efforts to reduce their production waste and use their resources more efficiently. The main data collection methods used for the study were secondary data research, discourse analysis, case studies, and focus group interviews. The analysis of the food waste management applications in the European countries’ food sub-sectors leads to the conclusion that since the national initiatives and success factors vary between the countries, it is important to invent such national food waste management systems that are economically justified and technically available for all enterprises regardless of their food waste production volumes. It is also necessary to raise awareness of the strategies that food industry employers, employees, and consumers can use to reduce their waste and thus promote a waste minimization culture in Europe. Doi: 10.28991/ESJ-2022-06-03-08 Full Text: PDF